Remote Sensing for a Changing Europe Proceedings of the 28th Symposium of the European Association of Remote Sensing Laboratories, Istanbul, Turkey, 2–5 June 2008 - Maktav, Derya (IOS Press, 2013)
The meeting welcomed 220 registered participants from all over the world. Eighty papers were presented during the symposium (2–5 June) at the 21 oral sessions including the three special sessions. As well, 60 papers were presented at the poster sessions which were also presented during two ‘oral communications’ sessions where the authors had the opportunity to present their poster papers for 4–5 minutes and invite the participants to visit their posters for detailed information. The ITU Süleyman Demirel Convention Center with one conference hall, one senate hall and four workshop rooms served for the event.